2008
DOI: 10.1007/s00120-008-1690-9
|View full text |Cite
|
Sign up to set email alerts
|

Kombinierte flexible und semirigide Ureterorenoskopie mit Laserlithotripsie

Abstract: As an alternative to percutaneous nephrolithotomy, repositioning of renal stones to the renal pelvis with the flexible instrument allows in selected cases safe laser fragmentation through a semirigid instrument. Access or exposition-related problems can be solved and repair costs of the instruments will be minimized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In a study involving 12 consecutive patients, 8 had total success, 3 had partial success, and 1 had residual fragments larger than 3 mm. Additionally, 88% of lower pole calyces were stone-free during the complication-free 3-month follow-up [15]. Miernik et al reported a primary stone-free rate of 63.2% and an overall computed tomography (CT) controlled stone-free rate after 3 months (including staged procedures) of 81.8% [16].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study involving 12 consecutive patients, 8 had total success, 3 had partial success, and 1 had residual fragments larger than 3 mm. Additionally, 88% of lower pole calyces were stone-free during the complication-free 3-month follow-up [15]. Miernik et al reported a primary stone-free rate of 63.2% and an overall computed tomography (CT) controlled stone-free rate after 3 months (including staged procedures) of 81.8% [16].…”
Section: Resultsmentioning
confidence: 99%
“…In a study involving 12 consecutive patients, 8 had total success, 3 had partial success, and 1 had residual fragments larger than 3 mm. Additionally, 88% of lower pole calyces were stone-free during the complication-free 3-month follow-up [ 15 ]. Miernik et al .…”
Section: Discussionmentioning
confidence: 99%